Influence of thiophene and furan π–bridge on the properties of poly(benzodithiophene-alt-bis(π–bridge)pyrrolopyrrole-1, 3-dione) for organic solar cell applications. (16th August 2021) - Agneeswari, Rajalingam; Kim, Danbi; Park, Seok Won; Jang, Soyeong; Yang, Hyun Seok; Shin, Insoo; Jeong, Jung Hyun; Tamilavan, Vellaiappillai; Jung, Yun Kyung; Park, Sung Heum
Abstract: A new polymer, P(BDT-fPPD), which incorporates 4, 8-bis(2-ethylhexyloxy)benzo[1, 2-b:4, 5-bʹ]dithiophene (BDT) and 4, 6-bis(furan-2-yl)-2, 5-dioctylpyrrolo [ 3, 4-c]pyrrole-1, 3(2H, 5H)-dione (fPPD, furan π–bridged PPD) units, was prepared. The optoelectrical, crystalline, charge transport, backbone curvature, and photovoltaic properties of P(BDT-fPPD) were thoroughly studied. P(BDT-fPPD) was also compared to the polymer P(BDT-tPPD), comprising BDT and 4, 6-bis(thiophen-2-yl)-2, 5-dioctylpyrrolo [ 3, 4-c]pyrrole-1, 3(2H, 5H)-dione (tPPD, thiophene π–bridged PPD) units. This study demonstrates that the π–bridges, such as thiophene and furan, attached between the BDT and pyrrolo [ 3, 4-c]pyrrole-1, 3(2H, 5H)-dione (PPD) units greatly altered the properties of the resulting polymers. In particular, the backbone curvature of P(BDT-fPPD) was significantly different from that of P(BDT-tPPD), which resulted in P(BDT-fPPD) having a higher bandgap energy ( E g ), deeper HOMO level, and higher crystallinity, but lower carrier mobility ( μ h ) and relatively poor power conversion efficiency (PCE) compared to P(BDT-tPPD) . For P(BDT-fPPD ), the E g, HOMO, μ h, and PCE were determined as 2.20 eV, −5.44 eV, 1.19 × 10 −5  cm −2  V −1  s −1, and 2.62%, respectively. The corresponding values for P(BDT-tPPD) were 2.11 eV, −5.39 eV, 2.95 × 10 −4  cm −2  V −1  s −1 and 5.29%, respectively. Interestingly, the inclusion of a small amount of P(BDT-tPPD ) in the PTB7-Th:PC70 BM blend enhanced the PCE of the resulting ternary organic solar cells (OSCs), whereas the insertion of P(BDT-fPPD) lowered the PCE of the ternary OSCs. The lower mobility and PCE obtained for P(BDT-fPPD) are mainly attributed to its poor blending with PC70 BM. Graphical abstract: Image 1 Highlights: New polymer namely P(BDT-fPPD) was prepared. The properties of P(BDT-fPPD) and P(BDT-tPPD) were compared. P(BDT-fPPD) and P(BDT-tPPD) showed s-type and linear curvature backbones. P(BDT-tPPD) provided higher PCE in binary and ternary OSCs than P(BDT-fPPD). The higher crystallinity of P(BDT-fPPD) provoked aggregation and offer low PCE.